State Power Legitimacy Crisis in the Era of Globalization - I. I. Osvetimskaya (Теоретическая и прикладная юриспруденция)
One of the urgent problems requiring special research is the comprehensive crisis of legitimacy that accompanies globalization, and one of the manifestations of which is the fragmentation of the phenomenon of legitimacy due to the fragmentation of the mechanisms of legitimation associated with different aspects of legitimacy being: power legitimacy, religion legitimacy, moral legitimacy, etc. State power legitimacy crisis has political and communicative grounds, such as: problematization of state sovereignty existence and state power existence; expanding political and non-political actors will to power; partial or complete lack of political will among citizens, which in turn is caused by a low level of public involvement in politics, which in turn is due to the usual functioning of political communication. The rules of language games (political, legal, cultural) are not created by the participants themselves in the result of a consensus-communicative discourse, but are set from the outside and are no longer shared by all members of a particular communicative community. The shaking of habitual traditions and norms of behavior leads to the imposed rules rejection and disruption of the consensus-communicative public discourse mechanisms functioning. These circumstances require a rethinking of the very phenomenon of power and the development of strategies for overcoming the crisis. From the point of view of a deliberative strategy (J. Rawls, J. Cohen, J. Habermas, S. Benhabib), the organization of a communicative power could become a way out of the crisis. This process requires all interested in the decision parties consensus expression. According to the agonistic strategy (C. Mouff), power is not interpreted as a purely external relation that develops between two given identities, but as something that establishes these identities themselves. According to J. Rawls and J. Habermas, it is necessary to find a way to eliminate power, because the more democratic a society is, the less power is present in its social relations. But according to C. Mouff, power relations are the basis of social relations, and the main issue of democratic politics is not how to eliminate power, but how to create such forms of power that could be more compatible with democratic values. Both approaches have the ability to bring the legitimacy of power out of the crisis, as long as the authorities will demonstrate its creative potential , which consists in protecting the fundamental rights of citizens; harmonious combination of public and private spheres; freedom realization.